A method for separating high purity chalcocite from copper ores

CN122999362APending Publication Date: 2026-10-30KUNMING UNIV OF SCI & TECH +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611416829.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

现有黄铜矿分离方法通常采用破碎、人工挑选、重选、磁选或浮选等方式,但对于低品位、细粒嵌布及多矿物共生的铜矿石,往往存在矿物解离不充分、杂质去除不彻底、所得黄铜矿纯度较低或回收效果不理想等问题

Benefits of technology

[0028]1)工艺协同互补,提纯精度较高。本发明首先通过重选,利用黄铜矿与石英、长石类矿物、云母类矿物、辉石类矿物、闪石类矿物、碳酸盐类矿物等低密度脉石矿物之间的密度差异,预先去除轻矿物并实现黄铜矿的初步富集;随后通过磁选和多级电磁选,利用黄铜矿与磁铁矿、黄铁矿、斑铜矿、黝铜矿、硫砷铜矿、辉钼矿、辉石、闪石等伴生矿物之间的磁性差异,进一步去除磁性杂质。重选与磁选、电磁选相互配合,可弥补单一分选方式杂质去除不充分的问题,有利于实现黄铜矿与伴生矿物的逐级分离,获得物相较为纯净、杂质含量较低的高纯度黄铜矿单矿物,满足矿物试验对样品纯度的要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999362A_ABST
    Figure CN122999362A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of mineral processing. The present application provides a method for separating high-purity chalcopyrite from copper ore, comprising: reducing and crushing the copper ore to-100 mesh, removing light minerals by elutriation, and then removing first magnetic minerals by magnetic separation; crushing the obtained heavy minerals to-180 mesh, and then performing three-stage electromagnetic separation under different magnetic field strengths, respectively, the first two stages of electromagnetic separation removing magnetic minerals and collecting non-magnetic materials, the third stage of electromagnetic separation removing non-magnetic products and collecting magnetic products, to obtain chalcopyrite rough concentrate with a purity greater than 90%; repeating the third stage of electromagnetic separation at least three times to obtain chalcopyrite single mineral with a purity greater than 98%. The present application utilizes the density and magnetic difference between different minerals for step-by-step separation, without adding chemical beneficiation reagents, which is conducive to improving the purity of chalcopyrite single mineral and reducing the influence on its original surface properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of mineral processing technology, and in particular to a method for separating high-purity chalcopyrite from copper ore. Background Technology

[0002] Copper, as a non-ferrous metal resource of significant strategic importance, is a crucial basic material for technological development, national defense, and national economic construction. Chalcopyrite is one of the main independent copper minerals and an important mineral raw material for industrial copper smelting and the recovery of associated resources such as sulfur and precious metals. Obtaining high-purity chalcopyrite is of great significance for conducting research on mineral processing mechanisms, improving the efficiency of copper ore resource utilization, and promoting the development of the metallurgical industry.

[0003] Natural copper ore is typically a complex system of multiple minerals coexisting. When using mixed ore samples to study mineral processing, metallurgical reactions, and mineral surface properties, other associated minerals can easily interfere with the experimental results, affecting the accuracy of the test data. High-purity chalcopyrite, with its relatively pure phase and homogeneous composition, can be used as an experimental sample to study the mineral processing behavior, metallurgical reaction characteristics, and reagent action patterns of chalcopyrite, providing a foundation for related process optimization and reagent development.

[0004] Currently, China lacks high-quality, high-purity chalcopyrite resources. Existing chalcopyrite separation methods typically employ crushing, manual sorting, gravity separation, magnetic separation, or flotation. However, for low-grade, fine-grained, and multi-mineral coexisting copper ores, these methods often suffer from insufficient mineral liberation, incomplete impurity removal, low purity of the obtained chalcopyrite, or unsatisfactory recovery results. When using chemical separation methods such as flotation, the reagents used may adsorb onto the chalcopyrite surface, altering the original surface properties of the mineral and thus affecting subsequent mineral mechanism studies and performance testing results.

[0005] Therefore, how to effectively separate and obtain chalcopyrite single minerals with low impurity content, high purity, and good preservation of the original physicochemical properties of chalcopyrite from copper ore remains a technical problem that needs to be solved in this field. Summary of the Invention

[0006] The purpose of this invention is to provide a method for separating high-purity chalcopyrite from copper ore, addressing the shortcomings of existing technologies.

[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0008] This invention provides a method for separating high-purity chalcopyrite from copper ore, comprising the following steps:

[0009] 1) The copper ore was reduced in size and crushed to obtain the first ore sample with a particle size of -100 mesh;

[0010] 2) The first mineral sample is washed to remove light minerals, yielding the first heavy mineral;

[0011] 3) Perform magnetic separation on the first mineral to remove the first magnetic mineral and obtain the second mineral;

[0012] 4) Crush the second mineral to -180 mesh to obtain the third mineral;

[0013] 5) Perform first-stage electromagnetic separation on the third mineral to remove the second magnetic mineral and obtain the first non-magnetic material;

[0014] The magnetic field strength of the first-stage electromagnetic separator is 4000~6000 A / m;

[0015] 6) Perform a second-stage electromagnetic separation on the first non-magnetic material to remove the third magnetic mineral, and obtain the second non-magnetic material;

[0016] The magnetic field strength of the second-stage electromagnetic selector is 10000~12000 A / m;

[0017] 7) Perform a third-stage electromagnetic separation on the second non-magnetic material to remove the obtained non-magnetic products, and collect the obtained magnetic products to obtain chalcopyrite rough concentrate with a purity greater than 90%.

[0018] The magnetic field strength of the third-stage electromagnetic selector is 15000~20000 A / m;

[0019] 8) Repeat the electromagnetic separation process of the chalcopyrite rough concentrate at least 3 times according to the third-stage electromagnetic separation conditions described in step 7). Each electromagnetic separation removes the non-magnetic products obtained, and the magnetic products obtained are used as the materials to be separated in the next electromagnetic separation to obtain chalcopyrite single mineral with a purity greater than 98%.

[0020] Preferably, the light minerals in step 2) include one or more of the following: quartz, feldspar minerals, mica minerals, pyroxene minerals, amphibole minerals, and carbonate minerals.

[0021] Preferably, in step 3), a magnet is used to perform magnetic separation on the first heavy mineral.

[0022] Preferably, in step 3), the first magnetic mineral includes magnetite and / or pyrrhotite.

[0023] Preferably, in step 5), the magnetic field strength of the first-stage electromagnetic selection is 5000 A / m.

[0024] Preferably, in step 6), the magnetic field strength of the second-stage electromagnetic selection is 11000 A / m.

[0025] Preferably, the second magnetic mineral in step 5) and the third magnetic mineral in step 6) both include one or more of biotite, dolomite, pyroxene, and amphibole.

[0026] Preferably, the magnetic field strength of the third-stage electromagnetic selection in step 7) is 18000 A / m.

[0027] The beneficial effects of this invention include the following:

[0028] 1) Synergistic and complementary processes result in high purification precision. This invention first utilizes gravity separation to remove light minerals and achieve preliminary enrichment of chalcopyrite by leveraging the density difference between chalcopyrite and low-density gangue minerals such as quartz, feldspar, mica, pyroxene, amphibole, and carbonate minerals. Subsequently, magnetic separation and multi-stage electromagnetic separation further remove magnetic impurities by utilizing the magnetic differences between chalcopyrite and associated minerals such as magnetite, pyrite, bornite, tetrahedrite, chalcopyrite, molybdenite, pyroxene, and amphibole. The combination of gravity separation with magnetic and electromagnetic separation compensates for the insufficient impurity removal of single separation methods, facilitating the step-by-step separation of chalcopyrite from associated minerals. This yields high-purity chalcopyrite with relatively pure phases and low impurity content, meeting the purity requirements of mineral testing.

[0029] 2) Pure physical separation is beneficial for preserving the original physical properties of minerals. This invention employs a physical separation process combining gravity separation, magnetic separation, and electromagnetic separation. During the separation process, no chemical beneficiation agents such as collectors, frothers, or modifiers are needed. This reduces the impact of chemical adsorption or chemical treatment on the surface properties of chalcopyrite and lowers chemical residues and secondary pollution. Therefore, it can better preserve the original physicochemical properties and crystal structure of chalcopyrite, providing more realistic and stable single-mineral samples for subsequent mineral mechanism research, surface property analysis, and performance testing.

[0030] 3) Strong resource adaptability and good separation effect. This invention uses staged crushing, gravity separation, and multi-stage gradient electromagnetic separation to gradually separate minerals of different particle sizes and magnetic minerals in copper ore. It can be used for the purification of chalcopyrite in low-grade, fine-grained, and multi-mineral coexisting copper ores. This combined separation process can improve the purity of chalcopyrite while reducing the adverse effects caused by the limited particle size or insufficient impurity removal caused by single separation methods, which is conducive to the fine separation and utilization of complex copper ore resources. Attached Figure Description

[0031] Figure 1 This is a process flow diagram of the present invention for separating high-purity chalcopyrite from copper ore. Detailed Implementation

[0032] This invention provides a method for separating high-purity chalcopyrite from copper ore, comprising the following steps:

[0033] 1) The copper ore was reduced in size and crushed to obtain the first ore sample with a particle size of -100 mesh;

[0034] 2) The first mineral sample is washed to remove light minerals, yielding the first heavy mineral;

[0035] 3) Perform magnetic separation on the first mineral to remove the first magnetic mineral and obtain the second mineral;

[0036] 4) Crush the second mineral to -180 mesh to obtain the third mineral;

[0037] 5) Perform first-stage electromagnetic separation on the third mineral to remove the second magnetic mineral, obtaining the first free mineral.

[0038] Magnetic materials;

[0039] The magnetic field strength of the first-stage electromagnetic separator is preferably 4000~6000 A / m, more preferably 4500~5500 A / m, and even more preferably 5000 A / m;

[0040] 6) Perform a second-stage electromagnetic separation on the first non-magnetic material to remove the third magnetic mineral, and obtain the second non-magnetic material;

[0041] The magnetic field strength of the second-stage electromagnetic separator is preferably 10,000~12,000 A / m, more preferably 10,500~11,500 A / m, and even more preferably 11,000 A / m;

[0042] 7) Perform a third-stage electromagnetic separation on the second non-magnetic material to remove the obtained non-magnetic products, and collect the obtained magnetic products to obtain chalcopyrite rough concentrate with a purity greater than 90%.

[0043] The magnetic field strength of the third-stage electromagnetic separator is preferably 15,000~20,000 A / m, more preferably 16,000~19,000 A / m, and even more preferably 18,000 A / m;

[0044] 8) Repeat the electromagnetic separation process of the chalcopyrite rough concentrate at least 3 times according to the third-stage electromagnetic separation conditions described in step 7). Each electromagnetic separation removes the non-magnetic products obtained, and the magnetic products obtained are used as the materials to be separated in the next electromagnetic separation to obtain chalcopyrite single mineral with a purity greater than 98%.

[0045] In this invention, the light mineral in step 2) is preferably one or more of the following: quartz, feldspar minerals, mica minerals, pyroxene minerals, amphibole minerals, and carbonate minerals; the feldspar minerals are preferably potassium feldspar and / or sodium feldspar; the mica minerals are preferably biotite and / or muscovite; and the carbonate minerals are preferably one or more of the following: calcite, dolomite, and ferro-dolomite.

[0046] In this invention, step 3) preferably involves using a magnet to perform magnetic separation on the first heavy mineral.

[0047] In this invention, step 3) preferably includes magnetite and / or pyrrhotite as the first magnetic mineral.

[0048] In this invention, the second magnetic mineral in step 5) and the third magnetic mineral in step 6) are preferably one or more of biotite, dolomite, pyroxene and amphibole.

[0049] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0050] The copper ore described in this invention originates from the Baironggangjiang mining area in Nyemo County, Tibet Autonomous Region. The raw copper ore contains 0.19% copper, 1.88% iron, 0.50% sulfur, 67.67% SiO2, 14.40% Al2O3, 3.86% K2O, 3.10% Na2O, 1.76% CaO, 1.23% MgO, and 5.41% other components. The main copper-bearing mineral in the ore is chalcopyrite, accompanied by pyrite, magnetite, and small amounts of bornite, tetrahedrite, arsenicite, molybdenite, and other metallic minerals, as well as non-metallic minerals such as quartz, potassium feldspar, sodium feldspar, biotite, muscovite, dolomite, pyroxene, and amphibole.

[0051] Example 1

[0052] The copper ore was thoroughly mixed and then fractionated using a quartering method until a copper ore sample weighing 2 kg was obtained. The fractionated copper ore was then crushed and sieved through a 100-mesh standard sieve.

[0053] The material was sieved, and the undersize material that passed through a 100-mesh standard sieve was collected to obtain the first particle size of -100 mesh.

[0054] Mineral sample.

[0055] Weigh 1 kg of the first mineral sample and add deionized water at a mass ratio of 1:8. Wash the sample at room temperature for 5 minutes each time, repeating the washing process 10 times. After each wash, remove the light minerals and collect the resulting heavy minerals. The light minerals are transparent minerals such as quartz, potassium feldspar, sodium feldspar, biotite, muscovite, and ferrodolithite. After washing, perform solid-liquid separation on the resulting heavy minerals, dry them at 105℃ for 2 hours, and then cool them to room temperature to obtain the first heavy mineral.

[0056] Magnetic separation of the first-grained mineral is performed using a U-shaped magnet. The magnetic field strength in the separation zone is 32000 A / m, the distance between the magnet and the material to be separated is 3 mm, the thickness of the material to be separated is 0.3 mm, the feed rate is 100 g, and the number of magnetic separations is 6. During the magnetic separation process, the first-grained magnetic mineral attracted by the magnet is removed, and the material not attracted by the magnet is collected to obtain the second-grained mineral. The first-grained magnetic mineral is magnetite.

[0057] The second mineral is crushed and sieved using a 180-mesh standard sieve. The material that passes through the 180-mesh standard sieve is collected to obtain the third mineral with a particle size of -180 mesh.

[0058] The third mineral undergoes a first-stage electromagnetic separation with a magnetic field strength of 5000 A / m, a separation gap of 10 mm, a feed rate of 2 g / min, and a throughput of 10 g per stage. During this first-stage electromagnetic separation, the second magnetic mineral is removed, and the resulting non-magnetic product is collected to obtain the first non-magnetic material. The second magnetic mineral consists of weakly magnetic minerals such as biotite, dolomite, pyroxene, and amphibole.

[0059] The first non-magnetic material undergoes a second-stage electromagnetic separation with a magnetic field strength of 11000 A / m, a separation gap of 10 mm, a feed rate of 2 g / min, and a processing volume of 10 g per stage. During the second-stage electromagnetic separation, the third magnetic mineral is removed, and the resulting non-magnetic product is collected to obtain the second non-magnetic material. The third magnetic mineral is a weakly magnetic mineral such as biotite, ferromagnetic dolomite, pyroxene, or amphibole.

[0060] The second non-magnetic material undergoes a third-stage electromagnetic separation with a magnetic field strength of 15000 A / m, a separation gap of 10 mm, a feed rate of 2 g / min, and a processing volume of 10 g per batch. The third-stage electromagnetic separation removes...

[0061] The non-magnetic product was obtained, and the magnetic product was collected to obtain chalcopyrite concentrate. Analysis showed that:

[0062] The chalcopyrite purity of the chalcopyrite rough concentrate is 95.58%.

[0063] The obtained chalcopyrite rough concentrate was used as the candidate material, and electromagnetic separation was repeated three times under the same conditions as the third-stage electromagnetic separation. In each electromagnetic separation, the non-magnetic product was removed, and the magnetic product was collected and used as the candidate material for the next electromagnetic separation. After the final electromagnetic separation, the magnetic product was collected to obtain high-purity chalcopyrite.

[0064] Scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) was used to detect chalcopyrite particles in copper ore. The SEM-EDS was an MLA650 with an accelerating voltage of 25 kV and a working distance of 10 mm. Mineral sections of the copper ore were prepared, and mineral particles were observed using backscattered electron imaging. The chalcopyrite particles were then identified and confirmed using EDS analysis. Twenty chalcopyrite particles were randomly selected from the copper ore, and three test points were randomly selected on each particle for EDS analysis. Test points avoided the edges, cracks, inclusions, and contact areas with other minerals. A total of 60 valid test points were obtained, yielding copper mass fraction data. The arithmetic mean of the copper mass fractions from these 60 valid test points was taken as the average copper mass fraction of the chalcopyrite particles in the copper ore. The results showed that the average copper mass fraction of the chalcopyrite particles in the copper ore was 35.31%.

[0065] The copper content in the obtained high-purity chalcopyrite single mineral was determined by chemical analysis. After thoroughly mixing the obtained high-purity chalcopyrite single mineral sample, three parallel samples were taken for analysis. The mass fraction of copper in each sample was determined, and the arithmetic mean of the three results was taken as the average mass fraction of copper in the obtained high-purity chalcopyrite single mineral. The results showed that the average mass fraction of copper in the obtained high-purity chalcopyrite single mineral was 34.72%.

[0066] The purity of chalcopyrite is calculated using the following formula: Chalcopyrite purity = Average mass fraction of copper in the obtained high-purity chalcopyrite single mineral ÷ Average mass fraction of copper in chalcopyrite particles in the raw copper ore × 100%. The calculated purity of the high-purity chalcopyrite single mineral obtained in this embodiment is 98.33%.

[0067] Example 2

[0068] The copper ore was thoroughly mixed and then reduced in size using a quartering method until the mass of the resulting copper ore sample was 2 kg. The reduced copper ore was then crushed and sieved using a 100-mesh standard sieve. The material that passed through the 100-mesh standard sieve was collected to obtain the first ore sample with a particle size of -100 mesh.

[0069] Weigh 1 kg of the first mineral sample, and add deionized water at a mass ratio of 1:10.

[0070] The sample was washed with deionized water at room temperature for 5 minutes each time, for a total of 12 washes. After each wash, light minerals were removed, and the resulting heavy minerals were collected. The light minerals included transparent minerals such as quartz, potassium feldspar, sodium feldspar, biotite, muscovite, and ferrodolithite. After washing, the resulting heavy minerals underwent solid-liquid separation and were dried at 105°C for 2 hours, then cooled to room temperature to obtain the first heavy mineral.

[0071] Magnetic separation of the first-grained mineral is performed using a U-shaped magnet. The magnetic field strength in the separation zone is 32000 A / m, the distance between the magnet and the material to be separated is 3 mm, the thickness of the material to be separated is 0.3 mm, the feed rate is 100 g, and the number of magnetic separations is 7. During the magnetic separation process, the first-grained magnetic mineral attracted by the magnet is removed, and the material not attracted by the magnet is collected to obtain the second-grained mineral. The first-grained magnetic mineral is magnetite.

[0072] The second mineral is crushed and sieved using a 180-mesh standard sieve. The material that passes through the 180-mesh standard sieve is collected to obtain the third mineral with a particle size of -180 mesh.

[0073] The third mineral was subjected to a first-stage electromagnetic separation with a magnetic field strength of 4000 A / m, a separation gap of 5 mm, a feed rate of 1 g / min, and a processing volume of 10 g per stage. During the first-stage electromagnetic separation, the second magnetic mineral was removed, and the resulting non-magnetic product was collected to obtain the first non-magnetic product. The second magnetic mineral consisted of weakly magnetic minerals such as biotite, dolomite, pyroxene, and amphibole.

[0074] The first non-magnetic material undergoes a second-stage electromagnetic separation with a magnetic field strength of 10000 A / m, a separation gap of 5 mm, a feed rate of 1 g / min, and a processing volume of 10 g per stage. During the second-stage electromagnetic separation, the third magnetic mineral is removed, and the resulting non-magnetic product is collected to obtain the second non-magnetic material. The third magnetic mineral is a weakly magnetic mineral such as biotite, dolomite, pyroxene, or amphibole.

[0075] The second non-magnetic material undergoes a third-stage electromagnetic separation with a magnetic field strength of 18000 A / m and a separation gap of [missing information].

[0076] The feed rate is 1g / min, and the throughput is 10g per batch. The non-magnetic products are removed during the third-stage electromagnetic separation process, and the magnetic products are collected to obtain chalcopyrite rough concentrate. Testing shows that the chalcopyrite purity of the rough concentrate is 96.20%.

[0077] The obtained chalcopyrite rough concentrate was used as the candidate material, and electromagnetic separation was repeated three times under the same conditions as the third-stage electromagnetic separation. In each electromagnetic separation, the non-magnetic product was removed, and the magnetic product was collected and used as the candidate material for the next electromagnetic separation. After the final electromagnetic separation, the magnetic product was collected to obtain high-purity chalcopyrite.

[0078] The average mass fraction of copper and the purity of the high-purity chalcopyrite obtained in this embodiment were determined and calculated according to the detection method described in Example 1. The test results show that the average mass fraction of copper in the obtained high-purity chalcopyrite is 35.06%, and the purity of chalcopyrite is 99.29%.

[0079] Example 3

[0080] The copper ore was thoroughly mixed and then reduced in size using a quartering method until the mass of the resulting copper ore sample was 2 kg. The reduced copper ore was then crushed and sieved using a 100-mesh standard sieve. The material that passed through the 100-mesh standard sieve was collected to obtain the first ore sample with a particle size of -100 mesh.

[0081] Weigh 1 kg of the first mineral sample and add deionized water at a mass ratio of 1:8. Wash the sample at room temperature for 7 minutes each time, repeating the washing process 10 times. After each wash, remove the light minerals and collect the resulting heavy minerals. The light minerals are transparent minerals such as quartz, potassium feldspar, sodium feldspar, biotite, muscovite, and ferrodolithite. After washing, perform solid-liquid separation on the resulting heavy minerals, dry them at 105℃ for 2 hours, and then cool them to room temperature to obtain the first heavy mineral.

[0082] Magnetic separation of the first-grained mineral is performed using a U-shaped magnet. The magnetic field strength in the separation zone is 32000 A / m, the distance between the magnet and the material to be separated is 3 mm, the thickness of the material to be separated is 0.3 mm, the feed rate is 100 g, and the number of magnetic separations is 5. During the magnetic separation process, the first-grained magnetic mineral attracted by the magnet is removed, and the material not attracted by the magnet is collected to obtain the second-grained mineral. The first-grained magnetic mineral is magnetite.

[0083] The second mineral is crushed and sieved using a 180-mesh standard sieve. The material that passes through the 180-mesh standard sieve is collected to obtain the third mineral with a particle size of -180 mesh.

[0084] The third mineral was subjected to a first-stage electromagnetic separation with a magnetic field strength of 6000 A / m, a separation gap of 8 mm, a feed rate of 1.5 g / min, and a throughput of 10 g per stage. During the first-stage electromagnetic separation, the second magnetic mineral was removed, and the resulting non-magnetic product was collected to obtain the first non-magnetic product. The second magnetic mineral consisted of weakly magnetic minerals such as biotite, ferromagnetic dolomite, pyroxene, and amphibole.

[0085] The first non-magnetic material undergoes a second-stage electromagnetic separation with a magnetic field strength of 12000 A / m, a separation gap of 8 mm, a feed rate of 1.5 g / min, and a throughput of 10 g per batch. During the second-stage electromagnetic separation, the following are removed:

[0086] The third magnetic mineral was obtained by collecting the resulting non-magnetic product, thus yielding a second non-magnetic substance. The third magnetic mineral...

[0087] The substances are weakly magnetic minerals such as biotite, dolomite, pyroxene, and amphibole.

[0088] The second non-magnetic material was subjected to a third-stage electromagnetic separation at a magnetic field strength of 20000 A / m, a separation gap of 8 mm, a feed rate of 1.5 g / min, and a processing volume of 10 g per stage. During the third-stage electromagnetic separation, the non-magnetic products were removed, and the magnetic products were collected to obtain chalcopyrite rough concentrate. Testing showed that the chalcopyrite purity of the rough concentrate was 95.29%.

[0089] The obtained chalcopyrite rough concentrate was used as the candidate material, and electromagnetic separation was repeated three times under the same conditions as the third-stage electromagnetic separation. In each electromagnetic separation, the non-magnetic product was removed, and the magnetic product was collected and used as the candidate material for the next electromagnetic separation. After the final electromagnetic separation, the magnetic product was collected to obtain high-purity chalcopyrite.

[0090] The average mass fraction of copper and the purity of the high-purity chalcopyrite obtained in this embodiment were determined and calculated according to the detection method described in Example 1. The test results showed that the average mass fraction of copper in the obtained high-purity chalcopyrite was 34.65%, and the purity of chalcopyrite was 98.13%.

[0091] Comparative Example 1

[0092] The method is basically the same as in Example 1, except that the second-stage electromagnetic separation is reduced, and the average mass fraction of copper in the final chalcopyrite is 31.55%, and the purity of chalcopyrite is 89.35%.

[0093] Comparative Example 2

[0094] The process is basically the same as in Example 1, except that the electromagnetic refining operation is repeated three times under the same conditions as the third-stage electromagnetic separation on the chalcopyrite rough concentrate. The final chalcopyrite has an average copper content of 33.75% and a purity of 95.58%.

[0095] In summary, this invention utilizes the density and magnetic differences between different minerals for stepwise separation, eliminating the need for chemical beneficiation agents. This approach helps improve the purity of chalcopyrite and reduces the impact on its original surface properties.

[0096] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for separating high-purity chalcopyrite from copper ore, characterized in that, It includes the following steps: 1) The copper ore was reduced in size and crushed to obtain the first ore sample with a particle size of -100 mesh; 2) The first mineral sample is washed to remove light minerals, yielding the first heavy mineral; 3) Perform magnetic separation on the first mineral to remove the first magnetic mineral and obtain the second mineral; 4) Crush the second mineral to -180 mesh to obtain the third mineral; 5) Perform first-stage electromagnetic separation on the third mineral to remove the second magnetic mineral and obtain the first non-magnetic material; The magnetic field strength of the first-stage electromagnetic separator is 4000~6000 A / m; 6) Perform a second-stage electromagnetic separation on the first non-magnetic material to remove the third magnetic mineral, and obtain the second non-magnetic material; The magnetic field strength of the second-stage electromagnetic selector is 10000~12000 A / m; 7) Perform a third-stage electromagnetic separation on the second non-magnetic material to remove the obtained non-magnetic products, and collect the obtained magnetic products to obtain chalcopyrite rough concentrate with a purity greater than 90%. The magnetic field strength of the third-stage electromagnetic separator is 15000~20000 A / m; 8) Repeat the electromagnetic separation process of the chalcopyrite rough concentrate at least 3 times according to the third-stage electromagnetic separation conditions described in step 7). Each electromagnetic separation removes the non-magnetic products obtained, and the magnetic products obtained are used as the materials to be separated in the next electromagnetic separation to obtain chalcopyrite single mineral with a purity greater than 98%.

2. The method for separating high-purity chalcopyrite from copper ore according to claim 1, characterized in that, Step 2) The light minerals include one or more of the following: quartz, feldspar minerals, mica minerals, pyroxene minerals, amphibole minerals, and carbonate minerals.

3. The method for separating high-purity chalcopyrite from copper ore according to claim 1, characterized in that, In step 3), a magnet is used to perform magnetic separation on the first heavy mineral.

4. The method for separating high-purity chalcopyrite from copper ore according to claim 1, characterized in that, Step 3) The first magnetic mineral includes magnetite and / or pyrrhotite.

5. The method for separating high-purity chalcopyrite from copper ore according to claim 1, characterized in that, Step 5) The magnetic field strength of the first-stage electromagnetic selector is 5000 A / m.

6. The method for separating high-purity chalcopyrite from copper ore according to claim 1, characterized in that, Step 6) The magnetic field strength of the second-stage electromagnetic selection is 11000 A / m.

7. The method for separating high-purity chalcopyrite from copper ore according to claim 1, characterized in that... It lies in, Step 5) The second magnetic mineral and Step 6) The third magnetic mineral both include one or more of biotite, dolomite, pyroxene and amphibole.

8. The method for separating high-purity chalcopyrite from copper ore according to claim 1, characterized in that, Step 7) The magnetic field strength of the third-stage electromagnetic selector is 18000 A / m.